Direct hybridization of Fe-MOF and polymer to fabricate iron oxide/carbon nanorod microsphere anodes for lithium-ion batteries - Park, Jongyoon; Lee, Giwook; Lim, Won Gwang; Kim, Tae Nam; Yoo, Chung Yul; Yu, Sungju; Yoon, Jonghee; Chun, Jinyoung; Hwang, Jongkook (Applied Surface Science, 2025)
Three-dimensional iron oxide/carbon composite materials with multiscale hierarchy are promising anodes for lithium-ion batteries (LIBs); however, their synthesis typically involves complicated multistep procedures. Here, we present a direct hybridization of Fe-nitrilotriacetic acid (FeNTA) metal–organic framework (MOF) with melamine resin (MR) as self-templates to fabricate spherical superstructures composed of iron oxide and nitrogen-doped carbon nanorods (ss-IONC-MR). This process balances the crystallization of FeNTA with the polymerization of MR by systematically controlling temperature, reaction time, and reactant concentrations. During pyrolysis, FeNTA retains its unique spherical superstructure, while MR acts as a nitrogen source and a structural reinforcement to maintain the morphological integrity of ss-IONC-MR. The confinement of Fe3O4 nanoparticles (5–10 nm) within the N-doped carbon matrix minimizes agglomeration during repeated cycling tests. The radially oriented 1D nanorod superstructures enhance electron transfer, while hierarchical meso/macropores reduce diffusion lengths, improve accessibility to active sites, and prevent structural collapse during conversion reactions. Consequently, ss-IONC-MR achieves a high specific capacity of ∼ 500 mAh g-1 at a current density of 1.0 A g-1, demonstrating excellent electrochemical properties as an anode material for LIBs. This approach provides a simple method for creating hierarchical MOF-derived materials, with potential applications in catalysis and energy storage.
Keywords: Carbon composites; Fe3O4/carbon composite; Hybridisation; Ion batteries; Lithium ions; Melamine-resin; Metalorganic frameworks (MOFs); Metal–organic framework-polymer; Nitrilotriacetic acid; Superstructure; Fe3O4/carbon composite; Hybridization; Lithium-ion battery; MOF-polymer; Superstructure